Prothrombin complex concentrate for reversal of oral anticoagulants in patients with oral anticoagulation-related critical bleeding: a systematic review of randomised clinical trials - Ovesen, Christian; Purrucker, Jan; Grundtvig, Josefine; Mikkelsen, Theis Bech; Gluud, Christian; Jakobsen, Janus Christian; Christensen, Hanne; Steiner, Thorsten (Scandinavian journal of trauma, resuscitation and emergency medicine, 2025)
Background: Swift reversal of oral anticoagulation is deemed essential for the outcome of patients with anticoagulation-related critical bleeding. The aim of this systematic review was to evaluate the benefits and harms of prothrombin complex concentrate (PCC) in patients with oral anticoagulants-related critical bleeding. Methods: For this systematic review CENTRAL, MEDLINE, Embase, LILACS, BIOSIS, Web of Science, and clinical trial registries were systematically searched. Clinical study reports were also requested from competent authorities. Eligible for inclusion were randomised clinical trials comparing PCC versus no intervention, placebo, or other reversal interventions in participants with critical bleeding related to ongoing treatment with vitamin K antagonist (VKA) or direct oral anticoagulants (DOAC). Pre-specified primary outcomes were all-cause mortality, health-related quality of life, and serious adverse events for which meta-analyses, Trial Sequential Analysis, and GRADE assessments were conducted. Results: Three trials, randomising a total of 291 participants, evaluated PCC against two different active comparators in participants with VKA-related critical bleeding, and two trials, randomising a total of 534 participants, evaluated PCC against two different active comparators in participants with factor Xa-related critical bleeding. Among participants with VKA-related critical bleeding, meta-analyses showed no evidence of a difference between PCC versus fresh frozen plasma (FFP) when assessing all-cause mortality (risk ratio [RR] 1.05; 95% confidence interval (CI) 0.27 to 4.05; low certainty), health-related quality of life (mean difference 1.04; 95% CI − 0.94 to 3.02; very low certainty), and serious adverse events (RR 1.33; 95% CI 0.94 to 1.88; very low certainty), but information is currently sparse. Among participants with factor Xa-related critical bleeding, PCC could not be shown superior or inferior to other reversal strategies (FFP or andexanet alfa) on any patient-relevant outcome, but information is currently sparse. Conclusion: Among participants with VKA or DOAC-related critical bleeding, evidence from randomised clinical trials is currently insufficient to establish if PCC is superior or inferior versus other interventions in decreasing the risk of undesirable patient-relevant outcomes or improving health-related quality of life.